SWEAT EQUITY: A CONTEMPORARY ANALYSIS OF LAND DISPOSSESSION OF BLACK FARMERS IN THE SOUTHERN UNITED STATES - Nicholas Armstrong (Washington University Journal of Law and Policy, 2024)
Black rural land ownership is not what it was once was and Black rural landowners own far less than what they could and should own. Upwards of ninety percent of Black rural landowners have been dispossessed of their land due to government agency failure, systemic discrimination, and private prejudice that has shaped the legal landscaped since Reconstruction. Without legislation or policy to protect Black rural landowners, a lack access to legal representation, debt, and poorly shaped federal relief make them more vulnerable to dispossession of their land. This note examines the history of land dispossession of rural Black American farmers through a survey of relevant case law and offers critiques of federal legislation such as the Civil Rights Act of 1964 and the Black Farmers Act. This Note argues that initiatives intended to provide relief for historic racialized injustices have no place in federal government legislation aimed at providing relief for the entirety of the American population. In response, this Note proposes the authors’ own recommendations for future policy initiatives which are aimed at effectively remedying injustices suffered by Black American farmers through institution of policies that prevent localized discrimination and target systems of injustice that have too long enabled racially prejudicial dispossession of land from Black rural landowners.
Keywords: Black Farmers; Land Ownership; Civil Rights